Study on the Diversity of Genotypic Varieties of Durum Wheat (Triticum Durum Desf.) In the Sub-Humid Region of El Harrouch, Algeria (Journal of Biodiversity Conservation and Bioresource Management, 2023)
The study on the yield parameters and the morpho-biometric characterization of twenty genotypic varieties of durum wheat (Triticum durum Desf.) was carried out in the sub-humid region of El Harrouch of Algeria. A descriptive sheet according to the recommendations of UPOV (2014-2017) and the calculation of the Shannon and Weaver diversity index was prepared with 27 qualitative characters and one quantitative character relating to the different parts of the ear. The yield parameters, such as number of plants/m2, herbaceous tillers, ear tillers, number of ears/m2, number of grains/ear, weight of 1000 grains, grains yield, harvest index, areal biomass, economic yield and straw yield showed a great diversity among these varieties. The Shannon and Weaver index (H') revealed a great diversity of all the studied genotypes (H'=0.52). The high polymorphic characters were the shape of the shoulder of the lower glume (H'=1), the curvature of the beak of the lower glume (H'=0.9), the length of the rachis of the ear (H'=0.87), the disposition barbs (H'=0.86), the length of the hairs of the grain brush (H'=0.84), the hairiness of the first article of the rachis of the ear (H'=0.84) and the length of the first article of the ear (H'=0.81). Based on study result, the varieties suitable to this agro-ecological conditions could be chosen for this region. It is concluded that the creation of descriptive sheets, the knowledge of production and adaptation parameters could be considered as precursors of high yield for economic needs and mastery of production techniques in improvement programs.J. Biodivers. Conserv. Bioresour. Manag. 2023, 9(1): 41-60